Representation of Forests in Pragya Nepali Aadhunik Katha: A Critical Inquiry - Poudel, Anupama (Literary Studies, 2024)
The portrayal of forests in literature has long captivated readers, evoking a spectrum of emotions including fear, mystery, and freedom, among others. This paper delves into the portrayal of forests in literature, particularly focusing on the narratives collected by the three volumes of Nepal Academy in Pragya Nepali Aadhunik Katha. Considering the adverse impact of climate change on forests, this paper argues that literature plays a crucial role in shaping societal perspectives and behaviors to combat climate crises. It argues for the inclusion of environmental themes, particularly forests, in literary works, advocating for their potential to inspire action and cultivate a sense of community engagement. The representation of forests in literature published by organizations such as Nepal Academy, a government body, could prove crucial in instigating behavioral changes among people and promoting sustainable choices that aid in combating the climate crisis. By analyzing the selected stories from the three volumes of Pragya Aadhunik Nepali Katha, this research explores the extent of agency given to forests as integral components of stories. The analysis will be contextualized within Michaels’ idea of “monoculture,” and other relevant discussions surrounding the climate crisis. The findings aim to highlight the importance of incorporating forests into literary narratives, encouraging an understanding of their significance among readers and policymakers alike.